Preparing social workers for emerging roles in police social work - Logan, Isabel; Madden, Robert; Solak, Matthew (Journal of Social Work Education, 2023)
Schools of social work must prepare social workers to meet the demands of the rapidly emerging field of police social work. This article reports on the experiences of a social work program’s partnership with a police department. The authors identify an integrative practice model of police social work, specifying social work roles at the baccalaureate and graduate levels, as well as ethical issues. The model is based on the social work competencies and law enforcement best practices. The authors analyze the experiences of placing students directly into law enforcement settings and make recommendations to create successful experiences for students, social workers, and police. The importance of strategic partnerships, communication, trust, and support in building strong relationships is also highlighted.
Keywords: dept.swk; peer-reviewed

911: Stabilization approaches used by police social workers - Logan, Isabel; Madden, Robert; Sallaku, Katherine (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Police social workers are crucial components of police departments when individuals or communities experience crises. They perform essential tasks, including well-being checks, crisis intervention, de-escalation, mediation, safety planning, referrals to community services, and other preventative measures to stabilize clients in crisis. The chapter will define police social work and give the reader insight into the stabilization approaches used by police social workers to prepare clients for their next level of care. The chapter begins with a brief history of the evolution of police social workers within the context of public policy and their most recent call to action to address mental health crises. The authors utilize a multi-tier approach to highlight stabilization approaches used by police social workers with a focus on empowering individuals, families, and communities to collaborate on solutions. The chapter uses case scenarios drawn from the experiences of police social workers and interns to demonstrate stabilization approaches. A racial equity, culturally responsive, and trauma-informed lens informs the approach to stabilizing client systems in law enforcement settings. © 2023, IGI Global. All rights reserved.
Keywords: dept.swk